1977
DOI: 10.1901/jaba.1977.10-573
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Token Economy on Dietary Compliance for Children on Hemodialysis

Abstract: Adherence to dietary restrictions is a recurring problem for children on hemodialysis. The effect of behavior modification in maintaining dietary control is reported for four patients aged 11 to 18 years. Weight gain, potassium level, and blood urea nitrogen were utilized as criteria measures. A token reinforcement program implemented by the hemodialysis team resulted in significant changes in the dietary pattern of the children. The average weight gain between dialysis sessions for the four subjects during tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

1979
1979
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 6 publications
1
20
0
3
Order By: Relevance
“…The pediatric population is grossly underrepresented and understudied in the interventional hemodialysis research. No RCTs have been performed in pediatric hemodialysis patients, and only 2 pediatric/adolescent hemodialysis quasiexperimental studies have been performed 39,40 . Therefore, generalizability to pediatric populations is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric population is grossly underrepresented and understudied in the interventional hemodialysis research. No RCTs have been performed in pediatric hemodialysis patients, and only 2 pediatric/adolescent hemodialysis quasiexperimental studies have been performed 39,40 . Therefore, generalizability to pediatric populations is limited.…”
Section: Discussionmentioning
confidence: 99%
“…These behavioral techniques have been reported to successfully increase the compliance of small groups of dialysis patients. Target behaviors of these intervention studies have included compliance with diet and fluid restrictions [34][35][36][37], decreased time to complete self-dialysis training [38], elimination of a phobic response to dialysis [39], and monitoring of blood clotting times on self-dialysis [40], Cummings et al [4] reported the largest and most methodologically sophisticated intervention study to date in HD patients using a pretest-posttest control group design. They measured mean serum K and IWG prior to intervention (Tl).…”
Section: Esrd Compliance Intervention Studiesmentioning
confidence: 99%
“…Improved dietary choices by the elderly (Stock & Milan, 1993), nutritional quality of food purchases , and dietary compliance of children on dialysis machines (Magrab & Papadopoulou, 1977) have been achieved through various combinations of prompts, feedback, and social reinforcement, although experimental difficulties limited some of the findings (Winett, Kramer, Walker, Malone, & Lane, 1988). Adherence to medical regimens and protocols is a major problem in behavior change programs.…”
Section: Healthmentioning
confidence: 99%